The genus Paraxantia Liu & Kang (Orthoptera: Tettigoniidae: Phaneropterinae: Vosiini) in Himalaya-Hengduan Mountains, revealing high diversity of species - Wu, Chao; Liu, Chun-Xiang (Zootaxa, 2023)
The genus Paraxantia was recorded to be distributed in south of China, previously including 11 species. After examining numerous specimens of Paraxantia, here, we first propose that the genus Paraxantia could be divided into three species groups, and describe two new species from Himalaya-Hengduan Mountains: P. angustipennis sp. nov. and P. nujiangensis sp. nov.. A key to the species group of Paraxantia, necessary illustrations and life images of Paraxantia species are presented. The distribution of Paraxantia in Himalaya-Hengduan Mountains is discussed and mapped.